Influence of Falling Height on the Behavior of Skid- Launching Free-Fall Lifeboat in Regular Waves - M.M Karim; K.S Iqbal; M.R.H Khondoker; S.M.H Rahman (Journal of Applied Fluid Mechanics, 2011)
This paper numerically investigated the influence of falling height on the behavior of the skid-launching free-fall lifeboat (FFLB) in regular waves. The boat has been treated as a rigid body when the differential equations of motion for the four falling phases, i.e., sliding or ramp phase, rotation phase, free-fall phase and water entry phase of the lifeboat were solved in the time domain. The hydrodynamic characteristics of the lifeboat has been studied for different falling heights such as H = 1.5m, 1.75m and 2.00m. Horizontal and vertical excursions and the rotation of the axis of the boat have been computed at different time along with its horizontal and vertical velocities. Hydrodynamic forces and accelerations at normal and axial directions have also been determined. At first the analysis has been done in still water and then in regular wave with amplitude of 0.5m and a period of 2.0 sec. In all of the cases, effects of regular wave are shown by comparing the results with those considering the falling of FFLB into calm water.